2000
DOI: 10.1177/0887403400011002004
|View full text |Cite
|
Sign up to set email alerts
|

Is Preferential Treatment of Female Offenders a Thing of the Past? A Multisite Study of Gender, Race, and Imprisonment

Abstract: Dramatic increases in the number of women incarcerated in state and federal prisons have led some researchers to conclude that differential sentencing of female offenders is a thing of the past. This study uses data on offenders convicted of felonies in Chicago, Miami, and Kansas City to address this issue. The authors find no evidence to support this “gender neutrality” hypothesis. In all three jurisdictions, women face significantly lower odds of incarceration than do men. The results also reveal that the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
222
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(247 citation statements)
references
References 34 publications
22
222
2
1
Order By: Relevance
“…Furthermore, women are more likely to sustain community ties (e.g., family) and are viewed as less likely to reoffend than men are (Daly, 1994). White male defendants also are viewed as less criminally involved and less likely than Black males to recidivate (Bridges & Steen, 1998;Spohn & Beichner, 2000). These perceptions likely result in women and in White men being considered as better candidates for probation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, women are more likely to sustain community ties (e.g., family) and are viewed as less likely to reoffend than men are (Daly, 1994). White male defendants also are viewed as less criminally involved and less likely than Black males to recidivate (Bridges & Steen, 1998;Spohn & Beichner, 2000). These perceptions likely result in women and in White men being considered as better candidates for probation.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating Albonetti's (1991) findings that a lack of information available to judges often results in them making decisions based on stereotypes and past experiences, Steffensmeier et al (1998) asserted that judges sometimes develop a "conceptual shorthand" where they use limited information (e.g., offense seriousness, gender, race) to draw conclusions about the three focal concerns. This theory has been widely used to explain racial and gender disparities in sentencing (e.g., Spohn & Beichner, 2000;Steffensmeier & Demuth, 2006;Steffensmeier et al, 1993;Steffensmeier et al, 1998). This perspective explains why Black male defendants were found to receive the harshest treatment, as those of minority and male status elicit the strongest perceptions of blame and dangerousness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because Blacks and Hispanics are viewed as being more dangerous while Whites are viewed as less likely to recidivate (Steffensmeier, 1980). Other sentencing studies found similar results (Demuth & Steffensmeier, 2004;Johnson, Ulmer, & Kramer, 2008;Spohn & Beichner, 2000;Steffensmeier & Demuth, 2001.…”
supporting
confidence: 70%